-4(2-3x)=2(3x-8)+2x

Simple and best practice solution for -4(2-3x)=2(3x-8)+2x equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -4(2-3x)=2(3x-8)+2x equation:


Simplifying
-4(2 + -3x) = 2(3x + -8) + 2x
(2 * -4 + -3x * -4) = 2(3x + -8) + 2x
(-8 + 12x) = 2(3x + -8) + 2x

Reorder the terms:
-8 + 12x = 2(-8 + 3x) + 2x
-8 + 12x = (-8 * 2 + 3x * 2) + 2x
-8 + 12x = (-16 + 6x) + 2x

Combine like terms: 6x + 2x = 8x
-8 + 12x = -16 + 8x

Solving
-8 + 12x = -16 + 8x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-8x' to each side of the equation.
-8 + 12x + -8x = -16 + 8x + -8x

Combine like terms: 12x + -8x = 4x
-8 + 4x = -16 + 8x + -8x

Combine like terms: 8x + -8x = 0
-8 + 4x = -16 + 0
-8 + 4x = -16

Add '8' to each side of the equation.
-8 + 8 + 4x = -16 + 8

Combine like terms: -8 + 8 = 0
0 + 4x = -16 + 8
4x = -16 + 8

Combine like terms: -16 + 8 = -8
4x = -8

Divide each side by '4'.
x = -2

Simplifying
x = -2

See similar equations:

| 14.2=-6.8+2d | | 98x+45=458 | | 3(10x+25)=315 | | 3x^4-21x+18=0 | | v-28=269 | | 10a-5(a-3)=15 | | -y+43=187 | | 7t-3(1+t)=-19 | | 5/6(6)+1/2=2/3 | | 0.372= | | -12(-3x)=42 | | 2/4+3=8-2/4 | | ax+bx+12=4 | | 1540+x(145.50)=3140.50 | | 6(12x+2)=72x-10 | | 102/3*128/9 | | 1/5(10h+15)+5 | | -3x-8y=12 | | 4x-12y=48 | | 6+12/x=-1 | | 1/10x-5=65 | | 9(3y+40)= | | -4(2-3x)=2(3x-8)2x | | p/6+9+14 | | f(b)=b^2+7b+13 | | 520+x(5)=550 | | (25r^2-35r+10)/(5r-2) | | 85/4*9-17+5699/6*8-6+173 | | 3(y+2)-4(2y-1)=8 | | 80=5u-15 | | -8+1y=-9 | | 2x^2y+3xy^2=0 |

Equations solver categories